A prospective case control study on metabolic syndrome in lichen planus in a tertiary care centre - Kurian, Girlly; S., Krishnan; P., Shakthi (International Journal of Research in Dermatology, 2017)
Background: Lichen planus is an autoimmune, inflammatory papulosquamous disease affecting skin and mucous membrane with a possible association with the parameters of metabolic syndrome. Methods: We carried out a hospital based case control study among patients attending DVL OPD during a period of 1.5 years (January 2015 - May 2016). Study population included 40 cases of LP and 80 age and sex matched controls. Relevant history, clinical examination and blood investigations were done. Diagnosis of MS was made based on IDF criteria. Results: There was no significant association between metabolic syndrome and lichen planus (p=0.292). Although there was higher prevalence of hypertension (47.5% vs. 27.5%, p=0.029), triglyceride level (25% vs. 10%, p=0.030) and low HDLC levels (65% vs. 45%, p=0.039). We could not establish significant association between FBS and waist circumference with LP. Conclusions: Though metabolic syndrome was not significantly associated with LP, its components such as hypertension, triglycerides and low HDLC levels were significantly associated with LP as per the study. Therefore patients with LP need to be screened to rule out each of these parameters to avoid later complications.